(untitled) (Tempo e Argumento, 2021)
Given the 2017 coup in Zimbabwe, a rare event in Southern Africa but sadly common in the rest of the continent, this paper discusses the beginnings of the politicization of the Zimbabwe Defence Forces (ZDF) during the 1980s. At the end of the country’s war for independence in 1980, the ZDF formed as an amalgamation of former Rhodesian state military personnel and insurgents from the liberation movements of the Zimbabwe African People’s Union (ZAPU) and the Zimbabwe African National Union (ZANU). Personnel from ZANU came to dominate Zimbabwe’s new military given the lack of a specific agreement over the integration process, their numerical superiority, and ZANU’s electoral success that gave it political power. During the ZDF integration exercise of the early 1980s, British advisors attempted to create a Western-style force but acted pragmatically while North Korean instructors helped create an overtly ZANU affiliated brigade and party militia. In addition, South African destabilization and the rapid departure of former Rhodesian officers gave way to the accelerated promotion of former insurgents mostly affiliated with the ZANU government. Lastly, the further ZANU-ization of the ZDF occurred within the context of operations in southwestern Zimbabwe where it eliminated ZAPU as an opposition political movement and committed atrocities, and in Mozambique where Zimbabwean troops cooperated with allies from overtly politicized armies of neighboring states